The Cancellation of Environmental License of PT. Semen Indonesia: A Strategic Environmental Assessment - Edy Lisdiyono (Faculty of Law, Hasanuddin University, 2017)
Debate over the construction of a cement factory in Rembang Regency between the community groups of Kendeng mountain care is in relation with the issuance of the environmental license No. 660.1/17 of 2012 by the Governor of Central Java. It had been declared null and void by the Supreme Court of the Republic of Indonesia based on the decision in the case register No. 99 PK/TUN/2016. The reason for the submission of the cancelation to the Environmental License of PT. Semen Indonesia in Rembang Regency, the community who cares about Kendeng mountains was because the process of submitting the mining licenses for the cement plant was not open and transparent to the community and it was feared that there would be environmental damages to the CAT area (Watuputih basin). In other words, to get the benefits, they are obliged to stay away from potential damage. Then, the urgency in the Strategic Environmental Assessment is as the Government instrument used as an instrument of prevention from pollution and/or environmental damage, and it becomes the basis for the policy of development plans and/or programs within a territory. Therefore, the mining of the cement factory of PT. Semen Indonesia in Kendeng mountains of Rembang Regency is in the CAT area (groundwater basin) based on findings of the Strategic Environmental Assessment Team. It is a protected area so that it potentially causes damage and the mining process must be stopped.